Peran UMKM Dalam Meningkatkan Produktivitas Dan Perekonomian Nasional Berbasis Masyarakat Secara Berkelanjutan - Sunny Samsuni; Suherman; Media Sucahya; Sulasno (CV. Multi Kreasi Media, 2025)
Community service program was carried out in the Kubang Sepat Inpres area, Cibeber Subdistrict, Cilegon City. This program aimed to enhance the capacity of MSME (UMKM) actors in product innovation, business legality, and digital marketing strategies. The implementation methods included observation, interviews, and documentation. Over eight meetings, MSME actors received direct training in creating Business Identification Numbers (NIB), promotional design (banners), product documentation, and website development as a digital marketing medium. The results showed that MSME actors had a better understanding of the importance of business legality and were able to utilize digital technology to expand their market reach. Additionally, MSME products became more visually appealing and accessible to consumers. This program had a positive impact on improving the quality of business operations and the professionalism of MSME actors.